View of Walkeshwar Temple and Ghats at Banganga - Ayan, Ghosh (2023)
Walkeshwar is named after Walkeshwar Temple, built in 1127 AD by the Shilahara rulers. This temple was destroyed in 1534 by the Portuguese and a new one was constructed in the 1720s by Ramaji Kamath, a Gaud Saraswat Brahmin. The temple was again reconstructed in the 1950s in its current location on the western edge of Banganga Tank.